A methodology for the evaluation of competition policy - Kai Hüschelrath; Nina Leheyda (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
The paper develops a methodology for the evaluation of competition policy. Based on the existing literature and experiences with policy evaluations in other areas of economic activity, the three-step / nine-building-blocks methodology provides guidance for evaluation projects and also assists in the identification of avenues for further academic research.
Keywords: L41; K21; 330; Competition Policy; Evaluation; Merger control; Cartel enforcement; Wettbewerbspolitik; Wirkungsanalyse; Wissenschaftliche Methode